Use of the optical lithography in the development of disposable carbon based electrodes - doi: 10.4025/actascitechnol.v35i1.11915 - Mello, Lucilene Dornelles (2012)
In this study, carbon-based electrodes for disposable use were constructed using the technique of optical lithography. The process consisted in the irradiation of UV light on a layer of photosensitive resin (SU-8 50) deposited on a substrate of PVC. The pattern obtained electrode was filled with carbon paste. The electrodes were characterized by cyclic voltammetric using the reversible system Fe(CN)63-/Fe(CN)64- in KCl 0.1 mol L-1 and electrochemical impedance spectroscopy (EIS). The electrodes showed an E°’ = ½ (Epa + Epc) » 229 (± 2) mV vs SCE (n = 4), with DEp » 235 (± 14) mV (n = 4). Other studies showed a linear behavior of the peak current (Ip) both anode and cathode with v1/2, probably due to diffuse contribution and/or electron transfer kinetics of the reaction. These parameters are in accordance to with those obtained for screen-printed electrode described in the literature. The good results obtained show the suitability of the electrodes for analytical applications such as development of sensors.